PEMBERDAYAAN SEKOLAH DAN KOMITE SEKOLAH (Studi Evaluasi Kebijakan Pada Program BOS Di Kabupaten Pacitan) - Sugeng Suryanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2016)
School Operational Aid (BOS) is a government policy through the Ministry of Education and Culture, which is fully authorized its management to the schools by referring to the conditions set by the government. Schools with School Committee work together in utilizing the BOS funds to improve access and quality of education. With the implementation of BOS policy on school, then it have need of evaluating the BOS policy which this studydiscuss the empowerment of schools and the School Committee in the management of BOS. The problems of this research are about how: (1). The level of policy performance of the BOS program; (2). The level of policy effectiveness of BOS program; (3). The level of policy outcome of the BOS program; (4). The policy impact of the BOS program. These four issues are analyzed in relation to empowerment of school and school committee. This research applied descriptive qualitative method, with the data in the form of descriptions of the activities, work systems or behaviors exist in Pacitan Education Department, Schools and the School Committee recipient of BOS funds as the subject of the research. Data obtained by interview, observation and documentation studies. From the data analysis and discussion, it is concluded as follows: First: The level of performance of the BOS policy have achieved the objectives which the BOS has been targeted to help the poor students and ease the burden of other students; Second: The level of efficiency indicates that with the lack of BOS funds schools can still carry out activities to reach the standard results; Third: The level of outcomes have succeeded in increasing APK, control for APS, graduates proceed to a higher level, the BOS fund management transparent and accountable, the increase of parents participation in helping schools, results of Nilai Ebtanas Murni (NEM) increases, an increasing number of schools are accredited B; Fourth: The impact of policy on the BOS program, among others, the increase in the Human Development Index (HDI), the increase in students passing the national exam and an increase in per capita income.Empowerment Schools and School Committee be realized where the school and the school committee has been undergoing development, strengthening the potential / power and independence.Keywords: empowerment, School and School Committee, Policy on the BOS program.